The trend in Management of Stable Burst Fracture of Thoracolumbar Spine with Intact Neurology among Members of the Association of Spine Surgeons of Nepal: A Survey - Chaudhary, Rajesh Kumar; Basel, Suman Kumar; Kaucha, Deepak; Barakoti, Ram Krishna (Nepal Orthopaedic Association Journal, 2023)
Introduction: The management of stable burst fracture of thoracolumbar spine with intact neurology is controversial. The radiological interpretation of such fractures differs among the surgeons and hence the treatment. So, this survey aims to study discrepancies in management of such fractures among the members of the Association of Spine Surgeons of Nepal (ASSN). Methods: Two representative cases of stable burst fracture with intact neurology (Case 1 AO type A3 and Case 2 AO type A4) were chosen by the authors. Questionnaire was formulated in Google form which also contained X-rays and CT scans of the cases. Google form was circulated among the members of ASSN. The response was recorded in excel and was analyzed. Results: Out of 67 members of ASSN, 55 (82.08%) responded the survey. 35 responders (63.63%) used both AO classification and TLICS. Majority of responders responded correctly as AO Type A3 and A4 burst fractures after looking at X-rays and CT scans of Case 1 and Case 2 respectively. Regardless of TLICS of 0-3 or 4 in both the cases, majority (81.81% in Case 1 and 78.18% in Case 2) chose surgical intervention. The degree of kyphosis for 48 respondents (87.27%), the level of fracture for 45 respondents (81.81%), bone quality for 41 respondents (74.54%), the severity of canal compromise for 40 respondents (72.72%) were some important factors in treatment decisions. Conclusion: The wide interobserver variability exists among members of ASSN in the management of stable burst fractures of the thoracolumbar spine with intact neurology